SENYAPAN DI DALAM GELAR WICARA THE TONIGHT SHOW STARRING JIMMY FALLON SUATU ANALISIS PSIKOLINGUISTIK - Lombogia, Giovanna Ester Gabriella; Kodong, Fentje; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis analysis entitled " Senyapan di dalam Gelar Wicara The Tonight Show Starring Jimmy Fallon Suatu Analisis Psikolinguistik" is about linguistic learning in a psycholinguistics view. In this study, the writer analyzes the types of pause, one of the forms of speech disfluency in the object of research, the host and the guest stars in the tv talk show The Tonight Show Starring Jimmy Fallon, presented in the transcript of the talk show aired on 1 May 2020 and 2 May 2020. Pauses during spontaneous conversations is very common in daily life. The theory used to support this research is the theory of FoxTree (1995) and Bortfeld et al (2001). This research is focused on the types of speech disfluency that are pauses, which consist of silent pauses and filled pauses. The purpose of this study is to identify the types of pauses that occur in the talk show, and to find out the causes of pauses that occur in it. This analysis applies a qualitative descriptive method. The stages carried out in this research process are collecting data by downloading the video talk show, taking data transcripts with subtitles, identifying forms of pauses, classifying forms of pauses, looking for the causes of pauses, and summarizing the results of the analysis. The results of this study are the total number of pauses produced by the speakers are 183 times. Silent pauses are produced in the amount of 123 times (67%) and filled pauses are 60 times (33%)Keywords: Pause, psycholinguistic analysis